Facial nerve paralysis caused by a T‐cell lymphoma. Issue 12 (15th September 2020) - Nachtsheim, Lisa; Wittersheim, Maike; Kreissl, Stefanie; Klussmann, Jens Peter; Grosheva, Maria
Key Clinical Message: Facial nerve paralysis due to the infiltration by a lymphoma is rare and the prognosis remains poor. If perineural spread and meningeosis are suspected, quick interdisciplinary diagnostic work‐up is recommended. It should include magnetic resonance imaging, biopsy of the lesion, bone marrow biopsy, and lumbar puncture. Therapy should be initiated immediately. Abstract : Facial nerve paralysis due to the infiltration by a lymphoma is rare and the prognosis remains poor. If perineural spread and meningeosis are suspected, quick interdisciplinary diagnostic work‐up is recommended. It should include magnetic resonance imaging, biopsy of the lesion, bone marrow biopsy, and lumbar puncture. Therapy should be initiated immediately.